2005
DOI: 10.1016/j.jcf.2005.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Mealtime behaviors in families of infants and toddlers with cystic fibrosis

Abstract: Direct observation of mealtime behaviors indicates that parents of infants and toddlers with CF engage in more mealtime management behaviors than parents of controls and that young children exhibit more behaviors incompatible with eating as the meal progresses. These findings highlight modifiable targets for behavioral and nutrition interventions that can be specifically designed for families of infants and toddlers with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 23 publications
1
35
1
Order By: Relevance
“…The nutritional status of our patients was adequate. We did not find the differences in the percent ideal weight between patient and control groups, as Powers et al (2005) indicated, doubtless because of the greater caloric intake of our patients, due principally to their increased intake of fats. Our patient group's pulmonary function was less adequate than that of the control group, having a mean value of 75.5 + 16.8%.…”
Section: Discussioncontrasting
confidence: 59%
“…The nutritional status of our patients was adequate. We did not find the differences in the percent ideal weight between patient and control groups, as Powers et al (2005) indicated, doubtless because of the greater caloric intake of our patients, due principally to their increased intake of fats. Our patient group's pulmonary function was less adequate than that of the control group, having a mean value of 75.5 + 16.8%.…”
Section: Discussioncontrasting
confidence: 59%
“…Recent behavior assessment research has found that toddlers, regardless of health status, are observed to exhibit challenging behaviors at mealtimes such as refusing food, leaving the table, and noncompliance to instructions to eat by their parents (Powers, Patton, Byars, Mitchell, Maynard, et al, 2002). The focus on increasing intake by 600 to 800 calories per day over a shorter time frame could allow for better management of specific behavior concerns, such as leaving the table, spitting out food, or parents relying primarily on coaxing and feeding their toddler.…”
Section: Discussionmentioning
confidence: 99%
“…Toddlerhood is also a developmental period when behavioral feeding problems are most likely to emerge and when parents are challenged by typical feeding issues such as neophobia, the development of self-feeding skills, and learning about the social rules related to eating (Linscheid & Rasnake, 2001). In fact, direct observation of family mealtimes indicates that toddlers with CF show a high frequency of challenging behaviors throughout the meal when compared to older children with CF (Powers, Patton, Byars, Mitchell, Maynard, et al, 2002). The combination of the extra demands for increased caloric intake and behaviors consistent with typical child development lead to greater parental stress, less adaptive family functioning, and less parental confidence in their abilities to manage mealtime behaviors in infants and toddlers with CF than in nonchronically ill controls (Mitchell, Powers, Byars, Dickstein, & Stark, 2002;Powers, Patton, Byars, Mitchell, Jelalian, et al, 2002).…”
mentioning
confidence: 99%
“…Families and CF health care professionals should be aware of the substantial impact of behavior on optimal nutrition. [124][125][126][127] Children who continue to be at nutritional risk despite having addressed pulmonary, social, and dietary factors should be referred to pediatric gastroenterologists, endocrinologists, and behavioral specialists for further evaluation and management. Gastrostomy tube feedings have been shown in older children and adults with CF to improve weight and pulmonary function.…”
Section: Nutritional Riskmentioning
confidence: 99%